Lower prevalence of disordered eating behaviours among Norwegian female athletes compared to non-athletes: a cross-sectional survey using the eating disorder examination questionnaire - Vedenpää, M.; Sagelv, E.; Torstveit, M.; Borch, K.; Osborne, J. (European Journal of Sport Science, 2025)
The purpose of this study was to report and compare the prevalence of disordered eating behaviours (DEBs) among Norwegian female athletes of different competition levels and sport types, and non-athletes of different physical activity levels. A total of 565 females (athletes: n = 189; non-athletes: n = 376) completed the Eating Disorder Examination Questionnaire 6.0 (EDE-Q). Athletes were categorised as recreational (n = 72), national (n = 94), or elite (n = 23), while non-athlete females were sedentary (n = 111) or physically active but non-competitive (exercisers: n = 265). A global EDE-Q score of > 2.5 was considered as increased risk of an eating disorder. Data were modelled using linear or logistic regression, adjusted for body mass index (BMI), age category, and education level. Global EDE-Q score was lower among recreational (mean [95% confidence interval]): (1.73 [1.31, 2.14]; p = 0.003; d = 0.50) and national-level athletes (1.89 [1.52,2.26]; p = 0.024; d = 0.39) compared to exercisers (2.47 [2.19,2.75]), with recreational athletes also scoring lower than sedentary females (2.43 [2.09,2.78]; p = 0.022; d = 0.47). Leanness focused sports had higher restraint (p = 0.046; d = 0.30) and eating concern (p = 0.025; d = 0.35) subscale scores compared to non-leanness focused sports. Recreational- or national-level athletes scored on average lower DEB symptoms using EDE-Q, compared to sedentary and physical-active non-athletes. No EDE-Q difference was found between competition levels. Leanness focused sport athletes were more concerned about eating behaviours and had higher restraint than athletes from non-leanness focused sports. These findings suggest that sport participation may be associated with lower or higher disordered eating symptoms, depending on competitive level and type of sport, highlighting the complexity of these relationships in physically active females.